Comparative study of development of latent fingerprint by using cost effective waste materials. (2022) - Lohar, Sneha; Aseri, Vinay; Godara, Vanisha; Kumari, Poonam; Nagar, Varad; Pandit, Pritam P.; Chopade, Rushikesh L.; Singh, Apoorva; Awasthi, Kumud Kant; Sankhla, Mahipal Singh; Kaur, Navjot; Singh, Gaurav Kumar
Abstract: The powder method is a quick and easy approach to the development of latent fingerprints on porous and nonporous surface. There are many Waste materials of plant-based (orange peels, lemon peels) that are used as a powder was applied to the latent fingerprints of different surfaces using a camel hairbrush. This research study focuses on these two types of powders that are used for the enhancement of ridge characteristics to personal identification. Prints are clearly shown on the porous and non-porous surfaces or photography was done with suitable contrast. This powder is cost-effective and nontoxic in nature. An eco-friendly approach to develop fingerprints by using natural colour produces by various plant-based waste materials and a very reliable technique to use in the crime scene.